Bleeding complications with the P2Y12 receptor antagonists clopidogrel and ticagrelor in the PLATelet inhibition and patient Outcomes (PLATO) trial - Becker, Richard C; Bassand, Jean Pierre; Budaj, Andrzej; Wojdyla, Daniel M; James, Stefan K; Cornel, Jan H; French, John; Held, Claes; Horrow, Jay; Husted, Steen; Lopez-Sendon, Jose; Lassila, Riitta; et al. (European heart journal, 2011)
AIMS More intense platelet-directed therapy for acute coronary syndrome (ACS) may increase bleeding risk. The aim of the current analysis was to determine the rate, clinical impact, and predictors of major and fatal bleeding complications in the PLATO study. METHODS AND RESULTS PLATO was a randomized, double-blind, active control international, phase 3 clinical trial in patients with acute ST elevation and non-ST-segment elevation ACS. A total of 18 624 patients were randomized to either ticagrelor, a non-thienopyridine, reversibly binding platelet P2Y(12) receptor antagonist, or clopidogrel in addition to aspirin. Patients randomized to ticagrelor and clopidogrel had similar rates of PLATO major bleeding (11.6 vs. 11.2%; P = 0.43), TIMI major bleeding (7.9 vs. 7.7%, P = 0.56) and GUSTO severe bleeding (2.9 vs. 3.1%, P = 0.22). Procedure-related bleeding rates were also similar. Non-CABG major bleeding (4.5 vs. 3.8%, P = 0.02) and non-procedure-related major bleeding (3.1 vs. 2.3%, P = 0.05) were more common in ticagrelor-treated patients, primarily after 30 days on treatment. Fatal bleeding and transfusion rates did not differ between groups. There were no significant interactions for major bleeding or combined minor plus major bleeding between treatment groups and age ≥75 years, weight <60 kg, region, chronic kidney disease, creatinine clearance <60 mL/min, aspirin dose >325 mg on the day of randomization, pre-randomization clopidogrel administration, or clopidogrel loading dose. CONCLUSION Ticagrelor compared with clopidogrel was associated with similar total major bleeding but increased non-CABG and non-procedure-related major bleeding, primarily after 30 days on study drug treatment. Fatal bleeding was low and did not differ between groups.